A yellow fever virus NS4B inhibitor not only suppresses viral replication, but also enhances the virus activation of RIG-I-like receptor-mediated innate immune response. - Zhao Gao; Xuexiang Zhang; Lin Zhang; Shuo Wu; Julia Ma; Fuxuan Wang; Yan Zhou; Xinghong Dai; Esther Bullitt; Yanming Du; Ju-Tao Guo; Jinhong Chang (PLoS Pathogens, 2022)
Flavivirus infection of cells induces massive rearrangements of the endoplasmic reticulum (ER) membrane to form viral replication organelles (ROs) which segregates viral RNA replication intermediates from the cytoplasmic RNA sensors. Among other viral nonstructural (NS) proteins, available evidence suggests for a prominent role of NS4B, an ER membrane protein with multiple transmembrane domains, in the formation of ROs and the evasion of the innate immune response. We previously reported a benzodiazepine compound, BDAA, which specifically inhibited yellow fever virus (YFV) replication in cultured cells and in vivo in hamsters, with resistant mutation mapped to P219 of NS4B protein. In the following mechanistic studies, we found that BDAA specifically enhances YFV induced inflammatory cytokine response in association with the induction of dramatic structural alteration of ROs and exposure of double-stranded RNA (dsRNA) in virus-infected cells. Interestingly, the BDAA-enhanced cytokine response in YFV-infected cells is attenuated in RIG-I or MAD5 knockout cells and completely abolished in MAVS knockout cells. However, BDAA inhibited YFV replication at a similar extent in the parent cells and cells deficient of RIG-I, MDA5 or MAVS. These results thus provided multiple lines of biological evidence to support a model that BDAA interaction with NS4B may impair the integrity of YFV ROs, which not only inhibits viral RNA replication, but also promotes the release of viral RNA from ROs, which consequentially activates RIG-I and MDA5. Although the innate immune enhancement activity of BDAA is not required for its antiviral activity in cultured cells, its dual antiviral mechanism is unique among all the reported antiviral agents thus far and warrants further investigation in animal models in future.